2009
DOI: 10.1093/deafed/enp005
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Academic Success Among Deaf College Students

Abstract: For both practical and theoretical reasons, educators and educational researchers seek to determine predictors of academic success for students at different levels and from different populations. Studies involving hearing students at the postsecondary level have documented significant predictors of success relating to various demographic factors, school experience, and prior academic attainment. Studies involving deaf and hard-of-hearing students have focused primarily on younger students and variables such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 39 publications
5
47
0
5
Order By: Relevance
“…Those pupils were also supplied with equipment that was inconsistently implemented during teaching. Consequently, degree of HL is an essential underlying factor for understanding the teachers' approaches to and usage of microphones, and confirm that the degree of disability impacts teachers' praxis, as other studies have found (Convertino et al 2009;Marschark, Lang, and Albertini 2002).…”
Section: The Importance Of the Pupils' Hearing Losssupporting
confidence: 75%
See 1 more Smart Citation
“…Those pupils were also supplied with equipment that was inconsistently implemented during teaching. Consequently, degree of HL is an essential underlying factor for understanding the teachers' approaches to and usage of microphones, and confirm that the degree of disability impacts teachers' praxis, as other studies have found (Convertino et al 2009;Marschark, Lang, and Albertini 2002).…”
Section: The Importance Of the Pupils' Hearing Losssupporting
confidence: 75%
“…Pupils with mild HL are often reported to be ignored because they are believed to have less need for support compared with pupils with severe HL (Convertino et al 2009;Marschark, Lang, and Albertini 2002). Some studies found that teachers reported that students with mild HL performed more poorly in school compared with students with severe HL, because of a less supportive setting (Most 2004;Wolf 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that factors associated with student academic success are numerous, including demographic, aptitude, communication, and audiological characteristics [37]. Thus, family relationship was found to play a unique and significant role in predicting academic success, suggesting that college students in Taiwan who reported having more problems in the area of family relationship were more likely to experience academic difficulties and have lower GPA scores [35].…”
Section: Students (Understand Cognitive Perception Of Students With Smentioning
confidence: 99%
“…Pregledom novijih istraživanja utvrđeno je da komunikacioni, porodični, audiološki faktori, prethodno školsko postignuće, kao i prethodna obrazovna sredina (redovan sistem obrazovanja, sistem obrazovanja za gluvu i nagluvu decu) mogu da utiču na akademski uspeh gluvih i nagluvih studenata tokom visokog obrazovanja (Convertino et al, 2009). Hauser i sar.…”
Section: Sistem Obrazovanja/zapošljavanja Pored Toga Neprilagođena unclassified
“…Dominantan način komunikacije ispitanika sa njihovim roditeljima i okolinom je verbalni, što je inače slučaj kod većine (neki podaci kazuju i preko 95%) gluve i nagluve dece koja dolaze iz čujućih porodica (Convertino et al, 2009;DeLana et al, 2007). Roditelji smatraju da govorni jezik približava, a gestovni jezik distancira naše ispitanike od tipične populacije i otežava njihovu socijalnu integraciju.…”
Section: Porodični Faktoriunclassified